2015
DOI: 10.1097/mpg.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Inflammation and Impact on Growth in Children With Cystic Fibrosis

Abstract: The pattern of intestinal inflammation in CF is unique and distinct from inflammatory bowel disease, with elevated faecal calprotectin but normal faecal S100A12 and osteoprotegerin concentrations. The severity of intestinal inflammation, based on faecal calprotectin, significantly correlates with poor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 40 publications
9
108
3
4
Order By: Relevance
“…2014; Dhaliwal et al. 2015). Severe inflammation was found in 19 subjects (63%), intermediate inflammation in 7 subjects (23%) and mild inflammation in 4 subjects (13%).…”
Section: Resultsmentioning
confidence: 99%
“…2014; Dhaliwal et al. 2015). Severe inflammation was found in 19 subjects (63%), intermediate inflammation in 7 subjects (23%) and mild inflammation in 4 subjects (13%).…”
Section: Resultsmentioning
confidence: 99%
“…Last but not least, some specific questions are not addressed in this animal model. First, the level of fecal calprotectin in children younger than 4-year-old, especially infant in the first year of life had several cut-off levels [53, 54], which are not addressed by this animal model. Second, a group for ovalbumin washout period was not included.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators also found significant associations between gut microbial communities (but not respiratory microbiota) and early‐life CF exacerbations indicating the crucial role of gut–lung cross‐talk in this chronic respiratory disease 160 . Apart from lung pathology, elevated levels of intestinal inflammatory markers have been reported in whole gut lavage (e.g., albumin, IgG, IgM, eosinophil cationic protein, neutrophil elastase, IL‐1β, IL‐8) 161 and faeces (e.g., calprotectin) 162 from young children with CF. The GI microbiome of CF patients has reduced richness and diversity beginning in early childhood (2 years) and continuing until late adolescence (17 years) 163 .…”
Section: The Role Of the Microbiome In Cfmentioning
confidence: 99%